FUNCTIONAL ASSESSMENT METHODS IN PATIENTS WITH COMBINED INJURIES OF THE NOSE AND PARANASAL SINUSES - Bakiyeva SH.X; Karimberdiyev B.I; Djurayev J.A; Soatov I.O (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract. Combined injuries of the nose and paranasal sinuses represent a significant clinical challenge due to their impact on both anatomical integrity and functional status. This study aims to evaluate the effectiveness of modern functional diagnostic methods in patients with such injuries. A total of 140 patients were examined using a комплекс of clinical, instrumental, and functional assessment techniques, including anterior rhinoscopy, rhinomanometry, olfactory testing, and computed tomography (CT). The results demonstrate that functional diagnostic methods provide critical information for determining the severity of impairment and guiding treatment strategies. Rhinomanometry and CT imaging were found to be the most informative tools for assessing nasal airflow and structural damage. Early functional evaluation improves treatment outcomes and reduces complications.